Are students information literate? - Lasić-Lazić, Jadranka (Array, 2005)
The article discusses the relationship between concepts of information and information technology literacy, both being labelled as "the ultimate literacy in the information society". While IT literacy is mainly defined as a skill-based literacy, information literacy embraces a whole conglomerate of values, attitudes, skills, knowledge and perspectives directed towards enabling for critical thinking, self-directed learning and the responsible consume of information, each of one necessary for intelligent existence in the information age. Through a survey, the authors will explore personal meanings and perceptions of information literacy among students from the Faculty of Philosophy. For this population infomration literacy is a central issue since it is a prerequisite for academic success, but will also be a pervasive aspect of every day work: many students from this faculty will be teachers and will prepare younger generations for life and work in an information society. Therefore the results could serve as an indicator for future educational practices and potential tendencies in Croatia's educational system. The results of the study will be analyzed in the light of contemporary features of Croatia's information policy, which is mainly directed towards technical information infrastructure which is not sufficient to let citizens use the benefits of information society.